Case-Control Study of Diarrheal Disease Etiology in a Remote Rural Area in Western Thailand - Bodhidatta, Ladaporn (The American Society of Tropical Medicine and Hygiene, 2010)
The objective was to assess the association of enteric pathogens in diarrheal disease in a remote rural area in Thailand. Stool specimens were collected from 236 children aged 3 months to 5 years with acute diarrhea (cases) and from 236 asymptomatic controls. Standard microbiologic methods, and enzyme immunoassay for viral pathogens, Giardia, and Cryptosporidium, were used to identify enteric pathogens with susceptibility testing by disk diffusion. Campylobacter, Plesiomonas, Salmonella, and enterotoxigenic Escherichia coli were commonly isolated from cases and controls (22% versus 25%, 10% versus 11%, 6% versus 9%, and 10% versus 6%, respectively). Only Shigella, rotavirus, and adenovirus were identified significantly more frequently in cases than controls (9% versus 0%, 18% versus 3%, and 16% versus 2%, respectively), whereas Giardia lamblia was detected less often in cases than controls. Most pre-school children were infested with enteric pathogens; laboratory-based studies are important to understand the epidemiology of enteric pathogens in remote areas among marginal populations.